Enterobius vermicularis infection among adults in a rural village, Nakhon Ratchasima: a note on stool examination findings with comments - V Wiwanitkit (Journal of Health Science and Medical Research (JHSMR), 2002)
Enterobius vermicularis is an important helminthic infection in rural areas of Thailand. We visited a rural village in Nakhon Ratchasima Province during May 2000. All 153 adult villagers in the village were examined for stool parasites. Intestinal parasites were recovered in 104 individuals, giving an infection rate of 68%. Most identified cases were infected with fluke parasite (99 cases, 64.7%). Only one case (0.65%) of Enterbius vermicularis infection was detected from the stool examination. In this study, we used the stool examination for detection of Enterobius infection, therefore, the estimated prevalence is probably lower than the true prevalence. However, the perianal Scotch tape test could not be applied to the adult population. In general, examination of the anogenital region is considered not polite and adult Thai people do not like to let anybody sees their stool, hence, we can expect a very poor compliance to the Scotch tape test. According to our study, although the stool examination is not recommended for Enterobius infection, detection of Enterobius egg from stool examination can be a good marker for the hygiene problem in the study area.